Cartografias do Programa Institucional de Bolsa de Iniciação à Docência (PIBID) de Geografia no Brasil: o desenho da política pública e seus saberes - Costa, Glauber Barros Alves (2019)
The proposal of this study rested in the interest in analyzing the Programa Institucional de Bolsas de Iniciação à Docência (Institucional Program of Scholarships for Teacher Formation) (PIBID), the largest teacher training policy program in the country, understandings its role as a public policy, as well as discussing and reflecting upon conceptions and knowledge of the subprojects and the coordinators of the program and discuss about the knowledges in the PIBID. Parting from the analyses completed on the subprojects of geography from around the country and the interviews with the coordinators of these subprojects, a documentary and later exploratory study was developed. The idea was to analyze the subprojects of the PIBID in Geography selected for the 2013 cycle, as this was the cycle with most geography subprojects registered and executed during the preparation of this thesis, as it was elaborated between 2014 and February of 2018. The study focused on the way in which the PIBID is organized throughout the country and how policy on teacher formation occurs. Following the analysis of the subprojects, a categorization of the former was conducted in accordance with the projects and the ideas presented. In this way, in a smaller universe of research, the study continued to the exploratory phase with semi-structured interviews. The thesis proposes a field study based on 5% of the submitted subprojects, interviewing the 09 coordinators to understand the teaching knowledge they held and that knowledge which is present in their projects. As a result, the investigation constructed a doctoral research project that presents a view of teaching formation in geography, with the PIBID as the central focus and guiding axis of the investigation, we are defending about immersion knowledge, the concept created in this research. So, we are showing an original research that we prove the PIBID is a important public policy, program to teachers trainee, student assistance and a important program to approximate university and schools. Therefore, an original study was proposed with a critical analysis perspective about this topic. It can be inferred that the subprojects of the PIBID primarily dealt with the teaching of geography, but a deviation in the formative function or even in the geographical science was observed in several subprojects. The development and mobilization of diverse areas of knowledge guided by the coordinators was observed to conceptualize the subprojects and thus various ideas about the reflection of this policy in Brazilian degrees can be understood. The results in this research appears like tematics maps, grafics, spread sheets and figures, the besides narratives collected from the coordinators, showing the importance for this program to the teacher training courses in Brazil.